DAMPAK PENURUNAN TICK SIZE TERHADAP KUALITAS PASAR DAN DETERMINAN LIKUIDITAS PASAR DI BURSA EFEK INDONESIA (STUDI KASUS TICK SIZE RP1,00 UNTUK SAHAM DENGAN HARGA KURANG DARI RP200,00) - Setyawasih, Rianti (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2011)
This paper investigates the implemented a new Rp1,00 tick size on December 16, 2006 in the Indonesia Stock Exchange. The empirical research was conducted using the cross-sectional multiple regressin from daily/intraday data. The new tick relative spread (RS) and depth-to-relative spread (DRS). From cross-sectional analysis, our findings indicate that trading frequency significantly affect the liquidity while stock prices and volatility does not affect the relative spread (liquidity)